Time-Varying Interdependencies of Tourism and Economic Growth: Evidence from European Countries - Mina Dragouni; George Filis; Nikolaos Antonakakis (FIW - Research Centre International Economics, 2013)
In this study, we employ the novel measure of a VAR-based spillover index, developed by Diebold and Yilmaz (2012) to investigate the time-varying relationship between tourism and economic growth in selected European countries. Overall, the findings suggest that (i) the tourism-economy relationship is not stable over time in terms of both its magnitude and direction, (ii) the relationship exhibits patterns in its magnitude and/or direction during major economic events, such as the Great Recession of 2007 and the Eurozone debt crisis of 2010, and (iii) the impact of these economic events on the relationship between the tourism sector and the economy is more apparent to Cyprus, Greece, Portugal and Spain, which are the European countries that have experienced the most severe economic downturn since 2009. These results are important to tourism actors and policy makers, suggesting that they should pay particular attention to this time-varying relationship and the factors that influence it when designing their tourism strategies. In addition, the findings of this study carry significant implications for researchers, as they underline a strand of the literature which deserves further attention.
Keywords: C32; F43; L83; O52; 330; Tourism-Led Economic Growth; Economic-Driven Tourism Growth; Spillovers; Time-Varying Relationship; Variance Decomposition; European Countries